Nature and Magic as Representation of “The Sami” — Sami Shamanistic Material in Popular Culture - Kalvig, Anne Kathrine (Religions, 2020)
This article examines how magic and nature become representations of both “the Sami” and “Sami shamanism” in animation films Frozen 2 and Klaus, in the television crime series Midnattssol (Midnight Sun) and in three Eurovision Song Contest contributions partly by Sami artists, containing joik. With a methodological ludism approach and with material theory, the article asks how “the Sami” and shamanism are made relevant as spiritual or religious categories within popular cultural products, and how (and why) spirituality is being constructed and communicated on a more general level in a time of eco-crisis, where there is a growing global interest in perceived shamanistic and animistic perceptions of the world, nature, and ourselves. publishedVersion